A method for preparing a coated modified sodium ion positive electrode material
Through the multi-element collaborative modification method, the multivalent coating agent and the matrix material of the sodium ion positive electrode material are used for high-temperature calcination, which solves the problem of difficult to control the coating amount and uniformity of the existing sodium ion positive electrode material, and achieves efficient improvement of the material and optimization of battery performance.
Patent Information
- Application Number
- CN202310578772.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-22
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-05-22
AI Technical Summary
The coating amount and uniformity of existing sodium ion positive electrode materials are difficult to control, and the coating effect is single, resulting in poor capacity and circulation performance of the material.
Using a multi-element synergistic modification method, through high-temperature calcination treatment and pulverization, the mass ratio of at least three valence states of coating agents to the matrix material meets specific conditions, and a sodium ion positive electrode material with multi-element synergistic effect is prepared.
It effectively improves the interface stability of the material, optimizes the circulation performance of sodium ion batteries, and improves the battery capacity and long circulation performance.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a method for preparing a coated and modified sodium ion positive electrode material. Background Art
[0002] With the continuous improvement of science and technology, people's demand for energy is increasing, and traditional fossil energy will cause serious environmental pollution when used. Therefore, clean and renewable new energy has become a hot spot for various countries to develop. In recent years, lithium-ion battery materials have been in short supply and raw material prices have continued to rise. Lithium resources are low in surface content and unevenly distributed, and from the perspective of long-term energy development, abundant raw material resources, high safety and low cost are required. In contrast, sodium resources are abundant in reserves, widely available, and evenly distributed around the world. Sodium-ion batteries are lower in cost and safer, and will be an important supplement to lithium-ion batteries in the future.
[0003] At present, the mainstream sodium-ion batteries are divided into three categories: layered oxides, phosphates and Prussian blue. Among them, layered oxides have always been a hot topic in sodium-ion battery research because of their high gram-to-weight ratio. However, layered oxides have problems such as poor air stability and low interface stability, which prevent them from being widely used. Researchers often develop multi-element materials and modify them through the synergistic effect of multiple elements, such as ternary materials copper iron sodium manganese oxide, nickel iron sodium manganese oxide, and quaternary materials copper nickel iron sodium manganese oxide, copper iron magnesium sodium titanate, copper nickel iron sodium manganese oxide, etc., as well as high-entropy materials with more element types, such as copper magnesium nickel iron manganese sodium titanate, etc. However, quaternary or even quinary materials, as well as higher-element materials, are often difficult to prepare and complex to industrialize due to the large number of element types, so they are not conducive to large-scale commercial applications. Therefore, how to effectively improve on the basis of existing binary and ternary materials has become one of the important directions for the development of sodium electric materials.
[0004] At present, the commonly used improvement schemes are mainly doping or coating elements. Doping elements often require a large mass ratio, so it is not easy to operate and the effective benefits are small. Therefore, a simpler improvement method is to perform trace coating on the surface of the base material. The current coating methods are divided into solid phase method and liquid phase method. Solid phase coating is simple and economical, but the coating amount and coating uniformity are difficult to control, and most coating schemes are concentrated on single element coating, and there is no synergistic effect. The liquid phase coating method is relatively complex and costly. Summary of the invention
[0005] In view of the above analysis, the embodiment of the present invention aims to provide a method for preparing a coated modified sodium ion positive electrode material, so as to solve at least one of the problems that the coating amount and coating uniformity of the sodium ion positive electrode material prepared by the prior art method are difficult to control, the coating effect is single, and the capacity and cycle performance of the material are poor.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] A method for preparing a coated modified sodium ion positive electrode material comprises the following steps:
[0008] (1) According to the molar ratio, 0.65≤Na≤1, 0≤Cu≤0.35, M=z, and the sum of the molar ratio of Cu and the molar ratio of M z is 1, weigh each metal source for use, and weigh at least three valence states of coating agents R1, R2, and R3 for use;
[0009] (2) calcining the reserved metal source at high temperature and crushing it to obtain a matrix material;
[0010] (3) adding a reserved coating agent to the base material, calcining it at high temperature, and crushing it to obtain the positive electrode material;
[0011] Among them, M must contain Mn and at the same time contain one or more of Ni, Fe, Mg, Al or Ti.
[0012] Furthermore, the high temperature calcination temperature in step (2) is 800-1000° C. and the time is 10-25 h.
[0013] Furthermore, the high temperature calcination temperature in step (3) is 800-1000° C. and the time is 10-25 h.
[0014] Furthermore, in step (1), the valence of the metal element in R1 is +2, the valence of the metal element in R2 is +3, and the valence of the metal element in R3 is +4 or +6.
[0015] Further, R1 includes Mg, Ca, Sr or Ba elements, R2 includes Al, La or Y elements, and R3 includes Ti, Zr or W elements.
[0016] Furthermore, the mass ratios of the three valence states of R1, R2, and R3 to the matrix material are λ1, λ2, and λ3, respectively, then β(λ1 / R 1D50 +λ2 / R 2D50 +λ3 / R 3D50 )=1 / R D50 , where 0.5≤β≤2, R D50 D is the base material 50 , R 1D50 , R 2D50 , R 3D50 The D of the coating agent with three valence states of R1, R2 and R3 are 50 .
[0017] Furthermore, R D503000~15000nm, R 1D50 , R 2D50 , R 3D50 All are 10 to 60 nm.
[0018] Furthermore, the particle size ratio satisfies: 0.0625% ≤ R 1D50 / R D50 ≤2%, 0.0625%≤R 2D50 / R D50 ≤2%, 0.0625%≤R 3D50 / R D50 ≤2%.
[0019] Furthermore, the particle size ratio satisfies: The particle size ratio satisfies: 0.125% ≤ R 1D50 / R D50 ≤1.67%, 0.125%≤R 2D50 / R D50 ≤1.67%, 0.125%≤R 3D50 / R D50 ≤1.67%.
[0020] Further, the mass ratio satisfies: 0.0625%≤λ1≤3.34%, 0.0625%≤λ2≤3.34%, 0.0625%≤λ3≤3.34%, and 0.0625%≤λ1+λ2+λ3≤3.34%.
[0021] Furthermore, the positive electrode material is generally formulated as Na x Cu y M z O2 / R, Na in the general formula x Cu y M z O2 is the base material, and R is the surface coating material;
[0022] Among them, M must contain Mn and one or more of Ni, Fe, Mg, Al or Ti, 0.65≤x≤1, 0≤y≤0.35, y+z=1, and R is prepared by a coating agent with at least three valence states of R1, R2, and R3.
[0023] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0024] (1) In the preparation method of the sodium ion positive electrode material of the present invention, the base material is Na, Cu, and M, according to the molar ratio of 0.65≤Na≤1, 0≤Cu≤0.35, M=z, and the sum of the molar ratio of Cu and the molar ratio of M z is 1, and the coating layer is prepared by coating agents of three valence states R1, R2, and R3. The present invention obtains a multi-element synergistically modified sodium ion positive electrode material by simple solid phase coating. The coating layer material generated on the surface of the sodium ion positive electrode material includes at least the main elements copper and manganese and at least three valence coating elements, and the homogeneous high entropy coating layer (Na / Cu / Mn / R1 / R2 / R3) of at least five multi-valence elements is accumulated, which can effectively improve the material interface stability and optimize the cycle performance of the sodium ion battery;
[0025] (2) The present invention has found through a large number of experiments that the particle sizes of the three valence states of the coating agent and the matrix material need to meet the following conditions: β(λ1 / R 1D50 +λ2 / R 2D50 +λ3 / R 3D50 )=1 / R D50 ; Mass ratio meets: 0.0625%≤λ1≤3.34%, 0.0625%≤λ2≤3.34%, 0.0625%≤λ3≤3.34%, and 0.0625%≤λ1+λ2+λ3≤3.34%; Particle size ratio meets: 0.0625%≤R 1D50 / R D50 ≤2%, 0.0625%≤R 2D50 / R D50 ≤2%, 0.0625%≤R 3D50 / R D50 ≤2%; within the above range, sodium ion batteries have higher capacity and long cycle performance.
[0026] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be achieved and obtained through the contents particularly pointed out in the description. DETAILED DESCRIPTION
[0027] The preferred embodiments of the present invention are described in detail below, which together with the embodiments of the present invention are used to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.
[0028] A specific embodiment of the present invention discloses a method for preparing a coated modified sodium ion positive electrode material, comprising the following steps:
[0029] (1) According to the molar ratio, 0.65≤Na≤1, 0≤Cu≤0.35, M=z, and the sum of the molar ratio of Cu and the molar ratio of M z is 1, weigh each metal source for use, and weigh at least three valence states of coating agents R1, R2, and R3 for use;
[0030] (2) calcining the reserved metal source at high temperature and crushing it to obtain a matrix material;
[0031] (3) adding a reserved coating agent to the base material, calcining it at high temperature, and crushing it to obtain the positive electrode material;
[0032] Among them, M must contain Mn and at the same time contain one or more of Ni, Fe, Mg, Al or Ti.
[0033] Compared with the prior art, the coating layer generated on the surface of the sodium ion positive electrode material prepared by the method of the present invention includes at least the main elements copper, manganese and at least three valence coating elements, and a homogeneous high-entropy coating layer (Na / Cu / Mn / R1 / R2 / R3) of at least five multivalent elements in total, which can effectively improve the material interface stability and optimize the cycle performance of the sodium ion battery.
[0034] Specifically, the high temperature calcination temperature in step (2) is 800-1000° C., and the time is 10-25 hours.
[0035] Specifically, the high temperature calcination temperature in step (3) is 800-1000° C., and the time is 10-25 hours.
[0036] Specifically, in step (1), the valence of the metal element in R1 is +2, the valence of the metal element in R2 is +3, and the valence of the metal element in R3 is +4 or +6.
[0037] Specifically, R1 includes Mg, Ca, Sr or Ba elements, R2 includes Al, La or Y elements, and R3 includes Ti, Zr or W elements.
[0038] In a preferred embodiment, R1 includes Mg or Sr elements, and R2 includes Al elements.
[0039] Where a specification is required, the coating agent is one or more of the oxides, hydroxides or carbonates of the corresponding metal.
[0040] Specifically, the mass ratios of the three valence states of R1, R2, and R3 to the matrix material are λ1, λ2, and λ3, respectively, then β(λ1 / R 1D50 +λ2 / R 2D50 +λ3 / R 3D50 )=1 / R D50 , where 0.5≤β≤2, R D50 D is the base material50 , R 1D50 , R 2D50 , R 3D50 The D of the coating agent with three valence states of R1, R2 and R3 are 50 .
[0041] It should be noted that β is a comprehensive correction coefficient that takes into account the particle size distribution, sphericity, and true density differences of the sphere.
[0042] Specifically, R D50 3000~15000nm, R 1D50 , R 2D50 , R 3D50 All are 10 to 60 nm.
[0043] Specifically, the particle size ratio satisfies: 0.0625% ≤ R 1D50 / R D50 ≤2%, 0.0625%≤R 2D50 / R D50 ≤2%, 0.0625%≤R 3D50 / R D50 ≤2%.
[0044] Specifically, the particle size ratio satisfies: The particle size ratio satisfies: 0.125% ≤ R 1D50 / R D50 ≤1.67%, 0.125%≤R 2D50 / R D50 ≤1.67%, 0.125%≤R 3D50 / R D50 ≤1.67%.
[0045] Specifically, the mass ratio satisfies: 0.0625%≤λ1≤3.34%, 0.0625%≤λ2≤3.34%, 0.0625%≤λ3≤3.34%, and 0.0625%≤λ1+λ2+λ3≤3.34%.
[0046] Specifically, the positive electrode material is generally formulated as Na x Cu y M z O2 / R, Na in the general formula x Cu y M z O2 is the base material, and R is the surface coating material;
[0047] Among them, M must contain Mn and one or more of Ni, Fe, Mg, Al or Ti, 0.65≤x≤1, 0≤y≤0.35, y+z=1, and R is prepared by a coating agent with at least three valence states of R1, R2, and R3.
[0048] It should be noted that in the present invention, x, y and z all represent the molar ratio of each element and satisfy Na x Cu y M z Charge balance of O2.
[0049] It should be noted that the optional elements of the surface coating material do not contain the main elements copper and manganese that appear in the matrix, so that the surface reaction of the positive electrode material can generate a high entropy coating layer (Na / Cu / Mn / R1 / R2 / R3). The present invention uses micron-sized layered oxides as positive electrode materials, and the coating agent is a nano-sized high-purity nano additive, the purpose of which is to evenly disperse the coating agent on the surface of the matrix.
[0050] The technical solution of the present invention is explained below in conjunction with specific embodiments.
[0051] In the following examples, sodium carbonate is selected as the sodium source, copper oxide is selected as the copper source, nickelous oxide is selected as the nickel source, ferroferric oxide is selected as the iron source, manganese dioxide is selected as the manganese source, and titanium dioxide is selected as the titanium source.
[0052] Example 1
[0053] A method for preparing a coated modified sodium ion positive electrode material comprises the following steps:
[0054] (1) According to the molar ratio, Na is 2 / 3, Cu is 1 / 3, M is Mn and Ti, wherein Mn is 2 / 3-0.01, and Ti is 0.01, weigh each metal source for use, and weigh at least three valence coating agents of Mg(OH)2, Al2O3 and TiO2 for use;
[0055] (2) calcining the reserved metal source at 900° C. for 20 h, and crushing the metal source to obtain a matrix material;
[0056] (3) Adding the reserved coating agent to the base material, calcining the base material at 850° C. for 10 h, and crushing the base material to obtain the positive electrode material.
[0057] Example 2
[0058] A method for preparing a coated modified sodium ion positive electrode material comprises the following steps:
[0059] (1) According to the molar ratio, Na is 0.8, Cu is 0.25, M is Mn and Fe, wherein Mn is 0.45, and Fe is 0.3, weigh each metal source and weigh at least three valence coating agents of SrCO3, Al2O3 and TiO2;
[0060] (2) calcining the reserved metal source at 900° C. for 20 h, and crushing it to obtain a matrix material;
[0061] (3) Adding the reserved coating agent to the base material, calcining the base material at 850° C. for 10 h, and crushing the base material to obtain the positive electrode material.
[0062] Example 3
[0063] A method for preparing a coated modified sodium ion positive electrode material comprises the following steps:
[0064] (1) According to the molar ratio, Na is 1, Cu is 0.01, M is Mn, Ni and Fe, wherein Mn is 0.33, Fe is 0.33, and Ni is 0.33, and each metal source is weighed for use, and at least three valence coating agents of Mg(OH)2, La2O3 and ZrO2 are weighed for use;
[0065] (2) calcining the reserved metal source at 900° C. for 20 h, and crushing the metal source to obtain a matrix material;
[0066] (3) Adding the reserved coating agent to the base material, calcining the base material at 850° C. for 10 h, and crushing the base material to obtain the positive electrode material.
[0067] Example 4
[0068] A method for preparing a coated modified sodium ion positive electrode material comprises the following steps:
[0069] (1) According to the molar ratio, Na is 0.9, Cu is 0.2, M is Mn, Ni and Fe, wherein Mn is 0.4, Ni is 0.1, and Fe is 0.3, weigh each metal source for use, and weigh at least three valence coating agents of Mg(OH)2, Al2O3 and ZrO2 for use;
[0070] (2) calcining the reserved metal source at 900° C. for 20 h, and crushing the metal source to obtain a matrix material;
[0071] (3) Adding the reserved coating agent to the base material, calcining the base material at 850° C. for 10 h, and crushing the base material to obtain the positive electrode material.
[0072] Example 5
[0073] A method for preparing a coated modified sodium ion positive electrode material comprises the following steps:
[0074] (1) According to the molar ratio, Na is 1, Cu is 0.04, M is Mn, Ni and Fe, wherein Mn is 0.33, Ni is 0.3, and Fe is 0.33, and each metal source is weighed for use, and at least three valence coating agents of SrCO3, Al2O3 and WO3 are weighed for use;
[0075] (2) calcining the reserved metal source at 900° C. for 20 h, and crushing it to obtain a matrix material;
[0076] (3) Adding the reserved coating agent to the base material, calcining the base material at 850° C. for 10 h, and crushing the base material to obtain the positive electrode material.
[0077] Example 6
[0078] A method for preparing a coated modified sodium ion positive electrode material comprises the following steps:
[0079] (1) According to the molar ratio, Na is 1, Cu is 0.1, M is Mn, Ni and Fe, wherein Mn is 0.33, Ni is 0.24, and Fe is 0.33, and each metal source is weighed for use, and at least three valence coating agents of Mg(OH)2, Y2O3 and TiO2 are weighed for use;
[0080] (2) calcining the reserved metal source at 900° C. for 20 h, and crushing it to obtain a matrix material;
[0081] (3) Adding the reserved coating agent to the base material, calcining the base material at 850° C. for 10 h, and crushing the base material to obtain the positive electrode material.
[0082] Example 7
[0083] The method for preparing the positive electrode material of this embodiment is the same as that of embodiment 1, except that the high temperature calcination temperature in step (2) is 800° C. and the calcination time is 25 h;
[0084] In step (3), the high temperature calcination temperature is 1000° C. and the calcination time is 25 hours.
[0085] Example 8
[0086] The method for preparing the positive electrode material of this embodiment is the same as that of embodiment 1, except that the high temperature calcination temperature in step (2) is 1000° C. and the calcination time is 10 h;
[0087] In step (3), the high temperature calcination temperature is 800° C. and the calcination time is 18 h.
[0088] The specific specifications of the positive electrode materials prepared in Examples 1-8 are shown in Table 1.
[0089] Table 1
[0090]
[0091] Comparative Example 1
[0092] The sodium ion positive electrode material and preparation method of this comparative example are the same as those of Example 3, except that the surface coating layer material does not contain R1.
[0093] Comparative Example 2
[0094] The sodium ion positive electrode material and preparation method of this comparative example are the same as those of Example 3, except that the surface coating layer material does not contain R2.
[0095] Comparative Example 3
[0096] The sodium ion positive electrode material and preparation method of this comparative example are the same as those of Example 3, except that the surface coating layer material does not contain R3.
[0097] Test Example 1
[0098] The base material and positive electrode material prepared in Examples 1-8 and the positive electrode material prepared in Comparative Examples 1-3 were made into sodium ion button batteries, and the specific method was as follows:
[0099] Assembly: The positive electrode material, conductive carbon black SP, and polyvinylidene fluoride (PVDF) are mixed and ground evenly in a mass ratio of 90:5:5, and NMP is added to the mixture to prepare a viscous glue; the glue is coated on aluminum foil, and after drying in a vacuum oven, it is used as a positive electrode plate, and the obtained positive electrode plate is further pressed, and a metal sodium plate is used as a negative electrode plate; a glass fiber film is used as a diaphragm, and an EC / DMC solution of sodium hexafluorophosphate is used as an electrolyte, and a button half-cell is assembled in the order of a positive electrode shell, a positive electrode plate, a diaphragm, a negative electrode, and a negative electrode shell.
[0100] Test: The prepared button half-cell was subjected to an electrical performance test at a voltage range of 2.5-4.0 V, with the gram capacity at 0.1C and 1C and the cycle retention rate at 1C rate as the evaluation basis, see Table 2 for details.
[0101] Table 2
[0102]
[0103]
[0104] It can be seen from Table 2 that the positive electrode material prepared in each embodiment has significantly improved battery capacity and retention rate after coating compared with the base material. Compared with comparative examples 1-3, the positive electrode material prepared in Example 3 has reduced battery capacity and retention rate if one less coating agent is added, which is not as good as the effect of adding three coating agents at the same time.
[0105] It can be seen from the results of Example 1 and Examples 7-8 that the same positive electrode material can be prepared by selecting different sintering temperatures and sintering times. Although this will result in different D50 and electrochemical properties of the base material, the coating can still achieve the effect of improving capacity and cycle retention rate.
[0106] The inventors have also conducted the above tests on other embodiments, and the results are basically the same. Due to limited space, they are not listed one by one.
[0107] Test Example 2
[0108] The positive electrode material was prepared by the method of Example 3, and R 1D50 , R 2D50 , R 3D50 The positive electrode material is prepared according to the size of λ1, λ2, and λ3. The specific parameter conditions are shown in Table 3. The sodium ion button battery and the test method are prepared according to the method of Experimental Example 1. The test capacity and retention rate results are shown in Table 4.
[0109] Table 3
[0110]
[0111]
[0112] Table 4
[0113]
[0114] It can be seen from Tables 3 and 4 that when β=1, it is the most ideal coating state and the coating effect is also the best. When β exceeds the range of 0.5 to 2, the coating effect will be reduced.
[0115] The above results show that the mass ratio of the three valence states of R1, R2, and R3 to the matrix material needs to satisfy β(λ1 / R 1D50 +λ2 / R 2D50 +λ3 / R 3D50 )=1 / R D50 , among which 0.5≤β≤2, the prepared positive electrode material has better performance.
[0116] The inventors have also conducted the above tests on other embodiments, and the results are basically the same. Due to limited space, they are not listed one by one.
[0117] Test Example 3
[0118] Only the values of λ1, λ2 and λ3 were changed, and the positive electrode material was prepared in the same manner as in Example 1. For specific parameters, see Table 5. Sodium ion button cells were prepared and tested according to the method of Experimental Example 1, and the test capacity and retention rate results are shown in Table 6.
[0119] Table 5
[0120]
[0121] Table 6
[0122]
[0123] As shown in Tables 5 and 6, when λ1, λ2 and λ3 are all less than 0.0625%, the coating amount is too little and the effect is not good. When λ1+λ2+λ3 is greater than 3.34%, the coating amount is too much, resulting in excessive surface impedance and a decrease in the coating effect. This shows that the positive electrode material prepared only has better performance when the added mass ratio of the coating agent is within the range of the present invention: λ1≥0.0625%, λ2≥0.0625%, λ3≥0.0625%, 0.0625%≤λ1+λ2+λ3≤3.34%.
[0124] The inventors have also conducted the above tests on other embodiments, and the results are basically the same. Due to limited space, they are not listed one by one.
[0125] Test Example 4
[0126] Change R 1D50 / R D50 , R 2D50 / R D50 and R 3D50 / R D50 The positive electrode material was prepared in the same manner as in Example 3. For specific parameters, see Table 7. The sodium ion button cell was prepared and tested according to the method of Experimental Example 1. The test capacity and retention rate results are shown in Table 8.
[0127] Table 7
[0128]
[0129] Table 8
[0130]
[0131] From Tables 7 and 8, we can see that R 1D50 / R D50 , R 2D50 / R D50 and R 3D50 / R D50 When the ratio is not between 0.125% and 1.67% as defined in the present invention, the capacity and retention rate of the prepared positive electrode material are reduced, and the optimal effect cannot be achieved.
[0132] The inventors have also conducted the above tests on other embodiments, and the results are basically the same. Due to limited space, they are not listed one by one.
[0133] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for preparing a coated modified sodium ion positive electrode material, characterized in that: The steps include: (1) According to the molar ratio, 0.65≤Na≤1, 0≤Cu≤0.35, M=z, and the sum of the molar ratio of Cu and the molar ratio of M z is 1, weigh each metal source for use, and weigh at least three valence states of coating agents R1, R2, and R3 for use; (2) calcining the reserved metal source at high temperature and crushing it to obtain a matrix material; (3) adding a reserved coating agent to the base material, calcining it at high temperature, and crushing it to obtain the positive electrode material; Among them, M must contain Mn and at the same time contain one or more of Ni, Fe, Mg, Al or Ti; R1 includes Mg, Ca, Sr or Ba, R2 includes Al, La or Y, and R3 includes Ti, Zr or W; The mass ratios of the coating agent with three valence states R1, R2, and R3 to the matrix material are λ1, λ2, and λ3, respectively. Then β(λ1 / R 1D50 +λ2 / R 2D50 +λ3 / R 3D50 )=1 / R D50 , where 0.5≤β≤2, R D50 D is the base material 50 , R 1D50 , R 2D50 , R 3D50 The D of the coating agent with three valence states of R1, R2 and R3 are 50 ; Particle size ratio meets: 0.0625% ≤ R 1D50 / R D50 ≤2%, 0.0625%≤R 2D50 / R D50 ≤2%, 0.0625%≤R 3D50 / R D50 ≤2%; The mass ratio satisfies: 0.0625%≤λ1≤3.34%, 0.0625%≤λ2≤3.34%, 0.0625%≤λ3≤3.34%, and 0.0625%≤λ1+λ2+λ3≤3.34%.
2. The method for preparing the coated modified sodium ion positive electrode material according to claim 1, characterized in that: The high temperature calcination temperature in step (2) is 800-1000° C. and the time is 10-25 hours.
3. The method for preparing the coated modified sodium ion positive electrode material according to claim 1, characterized in that: The high temperature calcination temperature in step (3) is 800-1000° C. and the time is 10-25 hours.
4. The method for preparing the coated modified sodium ion positive electrode material according to claim 1, characterized in that: In step (1), the valence of the metal element in R1 is +2, the valence of the metal element in R2 is +3, and the valence of the metal element in R3 is +4 or +6.
5. The method for preparing the coated modified sodium ion positive electrode material according to claim 1, characterized in that: Particle size ratio meets: Particle size ratio meets: 0.125% ≤ R 1D50 / R D50 ≤1.67%, 0.125%≤R 2D50 / R D50 ≤1.67%, 0.125%≤R 3D50 / R D50 ≤1.67%.
6. The method for preparing the coated modified sodium ion positive electrode material according to any one of claims 1 to 5, characterized in that: The positive electrode material is generally Na x Cu y M z O2 / R, Na in the general formula x Cu y M z O2 is the base material, and R is the surface coating material; Among them, M must contain Mn and one or more of Ni, Fe, Mg, Al or Ti, 0.65≤x≤1, 0≤y≤0.35, y+z=1, and R is prepared by a coating agent with at least three valence states of R1, R2, and R3.
Citation Information
Patent Citations
Positive electrode material, preparation method thereof and sodium ion battery
CN113937279A
Sodium-ion battery positive electrode material with multi-core type core-shell structure and preparation method of sodium-ion battery positive electrode material
CN114361415A